MANAGEMENT OF SUPRACONDYLAR FRACTURE OF HUMERUS IN CHILDREN BY CLOSE REDUCTION AND IMMOBILIZATION OF THE ELBOW IN EXTENSION AND SUPINATION - Babar, Iqtidar Ullah; Shinwari, Nowroz; Bangash, Mohammad Rahim; Khan, M Shoaib (Journal of Ayub Medical College Abbottabad, 2009)
Background: A Supracondylar fracture of the humerus is the most common fracture in children around the elbow and is also called first decade injury. If not treated properly it may lead to disability due to elbow stiffness, and sequel of neuro-vascular injuries like Volkmann ischemic contracture etc. This study was undertaken to determine the outcome of close reduction and immobilization of the elbow in extension and supination in displaced supracondylar fractures of the humerus in children. Method: This Quasi-experimental study was conducted in the Department of Orthopaedics, Postgraduate Medical Institute, Lady Reading Hospital Peshawar, from January 2007 to December 2007. The inclusion criteria was Gartland Type III (completely displaced) supracondylar fractures of the humerus and the exclusion criteria was open or closed Gartland type-III fracture associated with neurovascular injury. Close reduction under general anaesthesia was done and the elbow was immobilized in extension by the application of 2 plaster slabs according. The follow up is based on the overall rating using the modified Flynn global criteria. Results: Out of 70 cases, in 56 cases (80%), reduction was acceptable; while in 14 cases (20%) it was unacceptable. Those with unacceptable reduction, 2nd attempt of close reduction were done but only eight were successful and the other six children required open reduction and internal reduction. Those with acceptable reduction went in to union with the carrying angle ±5º of the contra-lateral side and full range-of-motion. Excellent result were achieved in 35 cases (50%), good in 15 cases (21.43%), fair in 4 cases (5.71%) and poor in 6 (8.75%) patients. Conclusion: The extension method of close reduction and immobilisation with two slabs is safe method and give better cosmetic results in uncomplicated type III injures as compared to the flexion method. Keywords: Supracondylar humeral fractures, Close reduction, extension method